Digital technologies and public life in Istanbul: Socio-demographic patterns and urban implications - Altanlar, Asli; Eren, Ibrahim; Aktan, Esin Ozlem Aktuglu (ELSEVIER SCI LTD, 2025)
Digital interactions have been observed to weaken physical social bonds, diminishing the sense of social belonging and fostering homogenized identities within online environments. This transformation in public spaces and social relationships demonstrates the reshaping effect of digitalization on social structures. This study examines the effects of digital technologies on societal life, encompassing dimensions such as social isolation, media influence, homogenization, placelessness, technology-induced social anxiety, and digital addiction. The findings are derived from descriptive analyses, t-tests, ANOVA, ANOVA-Bonferroni, and Post Hoc statistical methods applied to data from 400 participants aged 18 and over in Istanbul. The results reveal that the societal impacts of digital technologies are uniformly perceived across diverse age, education, and socio-economic groups. A notable gender distinction was observed in the dimensions of social isolation and digital addiction, with males scoring higher in these areas. At the same time, married individuals displayed higher levels of digital addiction than singles. These findings underscore that digitalization is driving profound shifts across all segments of society, increasingly shaping individuals' everyday lives.
Keywords: Digital technologies; Social isolation; Spatial belonging; Societal impact; Socio-demographic differences; ASSOCIATION; DEPRESSION; ATTACHMENT; Urban Studies